TINGKAT PENGETAHUAN, SIKAP DAN POLA KONSUMSI FAST FOOD SISWA SMA NEGERI 8 DENPASAR - Ni Wayan Reni Putri Sumantari; Desak Putu Sukraniti; I Made Purnadhibrata (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
Abstract. In this modern era there are many changes in our society, including the food pattern. Our society specially teenager that live in the big city, tend to consume fast food that have attractiveness , cheap in price, faster in serving, and have delicious taste but low nutrients than traditional food that rich in nutrients. Knowledge and attitude are very important to determine someone’s fast food pattern consumption. This research aims to knowing the knowledge, attitude and fast food pattern consumption at SMA Negeri 8 Denpasar. This was a cross sectional study that using 86 sample randomly. This research found that most of the sample have good knowledge about fast food (91,9%), and 51,2 % sample have good attitude towards fast food. The fast food pattern consumption contains total variety of fast food that the sample consume, fast food consumption frequency, also the total energy and protein from fast food that they consume. 51,2% sample have many kind of fast food that they consume and 60,5 % sample consume fast food in oftentimes. For the energy and protein consumption, 32,56 % sample have high energy consumption from their fast food and 25,6 % sample have high protein consumption from their fast food. From the cross tab analyze, it known that even there are many samples that have good knowledge about fast food but some of them still consume fast food oftentimes. That’s why researcher suggest the teacher or the other health worker to give some explanation to the students about fast food and nutrition and also motivate them to consume healthy food and reduce their fast food consumption.Keyword : knowledge , attitude, food consumption, fast food pattern